Become Captain of Your Financial Ship, Unit 4: Stay the Course - Josephine Turner (EDIS)
FCS7224, a 34-page curriculum by Josephine Turner, is Unit 4 in a series on personal financial management. It includes a slide presentation and information on consumer protection and regulations, such as those relating to credit identify theft and protection against consumer fraud, as well as information on garage sales, store sales, and warranties. Published by the UF Department of Family, Youth and Community Sciences, January 2007.